Production Improvement and Sugarcane-based Product Diversification of SMEs Yodhatama, Cendono Village, Kandat Sub-District, Kediri District - Ali, Dego Yusa; Astuti, Retno; Estiasih, Teti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2024)
Cendono Village is a sugarcane-producing village with sugarcane areas reaching 50% of agricultural land. The distinctive sugarcane products of Cendono Village are green sugarcane juice drinks and green sugarcane syrup, managed and produced by a productive youth group called Yodhatama. The processed products of this productive youth group are manufactured through a third-party manufacturing system at BUMDES Makmur Abadi, Bendosari Village, Blitar. Activities conducted include equipment facilitation, training and assistance in implementing aseptic sterilization and hot filling, product diversification, and process standardization. Diversification of green sugarcane processed products includes cup-packaged sugarcane juice drinks, jelly drinks, and jelly candies. Production training is conducted with equipment facilitation in the form of food dehydrators and cup sealers. Quality control and consistency are achieved through the development of Standard Operating Procedures (SOPs) and the implementation of Good Manufacturing Practices (GMP).